Meningkatkan Keterampilan Dasar Mengajar Guru Untuk Implementasi Manajemen Kelas Yang Bermutu - Azhar, Imam (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2022)
Teaching is a fulfilling profession. It recieves numerous rewards in the form of love, respect and trust from students and society. Teachers are the architects of a nation. They nurture the youth who are the future of a nation. They fashion the scientists, the innovators, the philanthropists and the leaders of tomorrow. Not everyone possesses the abilities of teachers. This profession ruquires a special set of skills, known “Basic Teaching Skills”. These skills are capabilities that enable someone to contribute and engage students’ learning fo the sake of students’success. These skills are essential at every step of the way, from creating leasson plans, and instructing learners to collaborating with others. The Basic Teaching Skills meant here are as follows; skill of opening and closing, questioning, empowering, making variation, explaining, teaching small group or individual, guiding small group discission, and managing the classroom. These Basic Teaching Skills should be improved day by day or time by time in order to achieve the goal of learning. Of the many basic teaching skills listed and improved, the quality of teaching can be gained, besides, the classroom management will be established successfully. This article is based on the literatures study.